Gyermekkorú bűnelkövetők és áldozatok - Mocsáry, Eszter (Debreceni Jogi Műhely, 2017)
In this article an evergreen topic will be discussed again and certainly not for the last time ...After the presentation on the children of the information society, – the "Z" generation currently living its childhood –, their specific problems and their living space, and after discussing the psychological and sociological background, legal history, and last but not least, the statistics, – I am looking for answers in my study such as what factors, data, precedents motivated the legislature to modify the punishable age for crime, furthermore, whether the more than three years since the entry into force of Law C of 2012 have confirmed the decision to be correct. I will also make mention of victims because of the considerable overlap between the perpetrator and the victim circles characterizing juvenile crime, showing the process which broadens the victims’ rights besides the ever stricter penal policy.Have hopes regarding the new regulations proven right? What else can the legislature do, and what can we do for our own children?